Ambulance clinicians implementing evidence-based practice: mind the gap! Attitudes, perceptions and experiences of student paramedics. - Newton, Jon; Smith, Andrew D. A. C. (British Paramedic Journal, 2023)
Background: Evidence-based practice (EBP) represents the conscientious and judicious use of the best contemporaneous evidence in partnership with patient values and clinical expertise to guide healthcare professionals. As a result, EBP is a recommended component of undergraduate education and considered fundamental for improving patient outcomes. EBP principles have thus become deeply rooted in higher education curricula, but only in recent years has this begun to permeate the world of paramedic practice. Despite this paradigm, the impact of EBP may be limited because ambulance clinicians may struggle with implementation, as a variety of barriers influence translation and application. Methods: A survey study aimed to gain insight into the epistemological and metacognitive barriers impacting student experience in order to help improve teaching and learning practices. Results: A sample of 64 students, across two different undergraduate paramedic science programmes, were recruited. Of these, 70% of BSc (Hons) students versus 33% of DipHE students agreed to some extent or greater that EBP represented minimal benefit in real-world practice due to Trust policy and the guidelines set out by the Joint Royal Colleges Ambulance Liaison Committee (Welch’s t = 2.571, df = 26, p = 0.016 two-sided). Furthermore, 25% felt standard operating procedures negatively impacted their ability to implement EBP, and 39% reported their EBP learning had improved their ability to implement improved levels of patient care. Conclusion: A disparity between theoretical learning and EBP implementation was identified. EBP may not dovetail with standard operating procedure within UK ambulance Trusts, resulting in confusion among student paramedics as to the true worth of EBP.